Analysis Of The Environmental Condition Of Areas Of High Technogenic Danger In Southwestern Uzbekistan. - Gulmurodov Farrukh Eshmurodovich; Polatov Asliddin Sayfullayevich (Genius Journals, 2024)
In the article, the environmental condition of the areas with a high man-made risk, the study of their negative impact on the land, and the tasks carried out on them are noted.
Keywords: Man-made disturbance; landscape; degradation